In-situ fabricated bulk metallic glass/graphite composites with a 3D lubricating layer: Tribological properties under dry sliding and in seawater. (August 2020) - Jiang, Xiaofang; Song, Junjie; Chen, Shuna; Su, Yunfeng; Fan, Hengzhong; Zhang, Yongsheng; Hu, Litian
Abstract: The bulk metallic glass has the potential application used in mechanical moving parts serving in corrosive environments because of its excellent mechanical, tribological properties and corrosion resistance. Here, Zr48 Cu36 Al8 Ag8 BMG/graphite composites with a 3D lubricating layer are prepared via an in-situ integrated technique. The synergism of the graphite lubrication and the micro-texture effect could significantly smooth the friction coefficient curve and reduce wear. Although seawater has a lubricating effect, the corrosion affects the reliability of BMG/graphite composites. By applying an external potential to the friction system, the effect of preventing galvanic phenomena at the interface between the alloy and graphite and improving the wear resistance of the composite material can be effectively achieved. Highlights: BMG/graphite self-lubricating composite was prepared via an in-situ integrated technique. The material has a 3D lubricating layer near surface. Graphite lubricating films and micro-textured effect improve tribological properties. Corrosion and wear resistance in seawater can further improved by applying an potential.